2009
DOI: 10.1371/journal.pgen.1000672
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Circulating Sphingolipid Concentrations in European Populations

Abstract: Sphingolipids have essential roles as structural components of cell membranes and in cell signalling, and disruption of their metabolism causes several diseases, with diverse neurological, psychiatric, and metabolic consequences. Increasingly, variants within a few of the genes that encode enzymes involved in sphingolipid metabolism are being associated with complex disease phenotypes. Direct experimental evidence supports a role of specific sphingolipid species in several common complex chronic disease proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
145
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(154 citation statements)
references
References 38 publications
8
145
0
1
Order By: Relevance
“…Such reagents would be especially powerful in combination with inducible enzymatic constructs that can be used to locally produce or degrade specific sphingolipid metabolites. Lastly, advances in human genetics may provide new insights into factors that regulate sphingolipid levels in health and disease (Hicks et al 2009;Demirkan et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Such reagents would be especially powerful in combination with inducible enzymatic constructs that can be used to locally produce or degrade specific sphingolipid metabolites. Lastly, advances in human genetics may provide new insights into factors that regulate sphingolipid levels in health and disease (Hicks et al 2009;Demirkan et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide association studies have shown a strong association of genetic SPTLC3 variants with alterations in lipid metabolism [29] and increased risk for myocardial infarction [30]. Therefore, lower C 16 SO levels might be directly or indirectly related to the increased risk of diabetic patients for developing cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…One such study reported increased odds of nephrolithiasis in isolated populations (25), which was attributed to the existence of consanguinity in some of the island populations (18,(26)(27)(28)(29)(30). Subsequent efforts in gene mapping in two of the Croatian Adriatic islands (Vis and Korčula) yielded a number of interesting results, including findings on genetic influence on height determination (31,32), lung function (33), chronic kidney disease (34), and levels of fasting glucose (35), serum lipids (36)(37)(38), creatinine (39), and plasma N-glycans (40), supporting the initial proposal that isolated populations present a very valuable and fundamentally advantageous research resource (17,18,41).…”
mentioning
confidence: 99%